Web-Based Honorarium Management Application for Contract Teachers at SMK Pelayaran Ampari Jayapura - Ansanay, Natalia Betty; Tatuhey, Emy Lenora (Jurnal Ilmiah Sistem Informasi, 2025)
Manual honorarium management for contract teachers in vocational schools often leads to inefficiencies, inaccuracies, and lack of transparency. This study aims to design and implement a web-based application for managing honorarium data for contract teachers at SMK Pelayaran Ampari Jayapura. The research employed the Waterfall model as the system development methodology, comprising requirement analysis, system design, implementation, and testing phases. Data were collected through interviews, observation, and literature review. The resulting application offers role-based access for school administrators, finance officers, and teachers, and features modules for attendance recording, automated honorarium calculation, digital payslip generation, and real-time reporting. System testing was conducted using Black Box Testing to validate system functionality and User Acceptance Testing (UAT) to assess user satisfaction. The results indicate that all ten system functions performed as expected, and 78.75% of users reported satisfaction with the system, with an average score of 4.1 out of 5. The implementation of this web-based system significantly improves administrative efficiency, payroll accuracy, and information transparency for stakeholders. The study contributes a holistic, user-centered solution that aligns with the goals of digital transformation in education and can serve as a model for similar implementations in other institutions.